Gesture and emotion: Can basic gestural form features discriminate emotions? - Kipp, M.; Martin, J.-C. (2009 3rd International Conference on Affective Computing and Intelligent Interaction and Workshops, 2009)
The question how exactly gesture and emotion are interrelated is still sparsely covered in research, yet highly relevant for building affective artificial agents. In our study, we investigate how basic gestural form features (handedness, hand shape, palm orientation and motion direction) are related to components of emotion. We argue that material produced by actors in filmed theater stagings are particularly well suited for such analyses. Our results indicate that there may be a universal association of gesture handedness with the emotional dimensions of pleasure and arousal. We discuss this and more specific findings, and conclude with possible implications and applications of our study.